Modeling and Analysis of Asymmetrical Faults for Relay Settings in Electric Power Protection System Learning - Abd. Hakim Butar-Butar; Agus Junaidi; Marwan Afandi; Sempurna Perangin-Angin; Rahmaniar (Britain International of Exact Sciences (BIoEx) Journal, 2022)
This study examines the analysis of Asymmetrical fault, namely single-phase ground faults for e-jobsheet products based on Information and Communication Technology (ICT) or utilizing computer programs for study. A study of short-circuit faults in the electric power system, is used to solve problems in the field of reliability and protection. the electric power system, namely the handling of single-phase short-circuit faults to ground which, if not neutralized, cause equipment damage to the electric power system. Parameters from modeling and analysis of asymmetrical faults are used for setting the Ground Fault Relay or often known as the Ground Fault Relay (GFR). The research study begins with modeling the interconnection system in the form of a reactance diagram, then modeling it with the bus impedance matrix equation, to determine the magnitude of the short circuit impedance value on the diagonal matrix. Then calculate the fault current of a single-phase short circuit to ground. From these results it is determined to determine the amount of the relay setting. The results showed that the asymmetrical fault current was 3.0 Pu with a setting time value of 2,45 seconds. The results of the study are used for learning relay settings. The simulation program was validated by experts, with a very good category with an Aikensv index of 0.872.